Seasonal Distribution of Sheeppox Cases in Lambs in Eastern Turkey - Eroksuz, Y.; Bulut, H.; Gulacti, I.; Ceribasi, A. O. (Medwell Online, 2008)
Sheeppox is an endemic disease in Turkey and cause significant economical losses. Although sheeppox cases can be seen in Turkey during various periods in a year, the cases occurring in the March-April period are the most prevelant in lambs of approximately one and half months of age. The objective of the present study was the virological, pathological and epidemiological investigation of the seasonal cases that cause high mortality in lambs. Following the clinical and pathological examinations of the cases, DNAs extracted from the samples were amplified by the Polymerase Chain Reaction (PCR) and PCR products were sequenced. According to PCR and sequence results, it was confirmed that the lambs were infected with sheeppox virus. In the anamnesis, it was reported by the owners of the animals that the mother ewes of the affected lambs had been in the pasture before the occurrence of the disease. Therefore, it could be concluded that being in the pasture for mother ewes for a period of time plays a major role in the epidemiology of the seasonal cases. In addition, lambs can play a role in the spread and maintenance of the virus in the environment.
Keywords: Sheeppox disease; polymerase chain reaction; lamb; pasture